Model Perancangan Sistem Pemesanan Tiket Bus Antar Kota Antar Propinsi Khusus di Cabang - Pangestu, Harijanto (ComTech: Computer, Mathematics and Engineering Applications, 2013)
At certain moments, especially on national holiday transportation users greatly increase. The manual ticket booking system of inter-city buses is not very effective and efficient as indicated that it takes long time to book tickets and find information about ticket availability for a specific purpose on a certain day. Besides, inaccuracies often happen on synchronizing ticket availability with seat availability. Due to those problems, it needs to be made a model of ticketing information system of inter-city buses. The initial phase focused on booking tickets at a branch office. The next stage of development is integrating the  information system of all branch offices to the central office. The purpose of this paper is to create a model of the system design if inter-city bus ticket reservation in inter-provincial branches can provide convenience for the branch to book tickets booked by customers. The methodology used in this research is a preliminary study by library research, followed by analysis on running systems through survey findings, then identification of information needs. From the results of this study it is found that a more specific design and implementation are expected to be made so as to provide more benefits to its users. The results of this study can be further developed and integrated with the central office.